2016
DOI: 10.1016/j.bpj.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Sustained α -catenin Activation at E-cadherin Junctions in the Absence of Mechanical Force

Abstract: Mechanotransduction at E-cadherin junctions has been postulated to be mediated in part by a force-dependent conformational activation of a-catenin. Activation of a-catenin allows it to interact with vinculin in addition to F-actin, resulting in a strengthening of junctions. Here, using E-cadherin adhesions reconstituted on synthetic, nanopatterned membranes, we show that activation of a-catenin is dependent on E-cadherin clustering, and is sustained in the absence of mechanical force or association with F-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 72 publications
2
39
1
Order By: Relevance
“…Low diffusivity promoted clustering and active nucleation, allowing junction formation to proceed. Within junctions, FRAP revealed that cadherins had low turnover and instead were immobilized within stable junctions [27]. Surprisingly, mechanical resistance alone was insufficient to form adherens junctions.…”
Section: Mechanobiology Of Adhesion Revealed Using Supported Lipidmentioning
confidence: 99%
See 3 more Smart Citations
“…Low diffusivity promoted clustering and active nucleation, allowing junction formation to proceed. Within junctions, FRAP revealed that cadherins had low turnover and instead were immobilized within stable junctions [27]. Surprisingly, mechanical resistance alone was insufficient to form adherens junctions.…”
Section: Mechanobiology Of Adhesion Revealed Using Supported Lipidmentioning
confidence: 99%
“…SLBs with reduced fluidity by the addition of high density poly-His E-cadherin ectodomain also supported AJ formation and were used to study α-catenin mechanobiology in cadherin-mediated adhesions [27]. Cells spread on these SLBs exhibited two populations of cadherins that clustered during filapodial retraction: AJs at the cell periphery and cadherins loosely clustered in “central adhesions” underneath the cell.…”
Section: Mechanobiology Of Adhesion Revealed Using Supported Lipidmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, the desmosome/IF linkage at cell–cell junctions has also been shown to regulate not only traction forces at cell–ECM adhesions, but also modulate forces at cell–cell junctions [21]. Using a combined approach of micropost arrays and AFM, epithelial cells with genetic mutation of a desmosome/IF linker molecule, DP, which lacks the IF-binding domain, exhibited significantly reduced traction forces and potentially increased tension or conformational changes in α -catenin of AJs [21,116]. This evidence lends support to the notion that abundant molecular communication exists between the two mechanically active junctional complexes [117].…”
Section: Techniques To Study Cell–cell Adhesionmentioning
confidence: 99%